MVCT versus kV‐CBCT for targets subject to respiratory motion: A phantom study - Baran, Geoffrey; Dominello, Michael M.; Bossenberger, Todd; Paximadis, Peter; Burmeister, Jay W. (Journal of applied clinical medical physics, 2021)
The use of kilovoltage cone‐beam computed tomography (kV‐CBCT) or megavoltage computed tomography (MVCT) for image guidance prior to lung stereotactic body radiation therapy (SBRT) is common clinical practice. We demonstrate that under equivalent respiratory conditions, image guidance using both kV‐CBCT and MVCT may result in the inadequate estimation of the range of target motion under free‐breathing (FB) conditions when standard low‐density window and levels are used. Two spherical targets within a respiratory motion phantom were imaged using both long‐exhale (LE) and sinusoidal respiratory traces. MVCT and kV‐CBCT images were acquired and evaluated for peak‐to‐peak amplitudes of 10 or 20 mm in the cranial‐caudal direction, and with 2, 4 or 5 s periods. All images were visually inspected for artifacts and conformity to the ITV for each amplitude, period, trace‐type, and target size. All LE respiratory traces required a lower threshold HU window for MVCT and kV‐CBCT compared to sinusoidal traces to obtain 100% volume conformity compared with the theoretical ITV (ITVT). Excess volume was less than 2% for all kV‐CBCT contours regardless of trace‐type, breathing period, or amplitude, while the maximum excess volume for MVCT was 48%. Adjusting window and level to maximize conformity with the ITVT is necessary to reduce registration uncertainty to less than 5 mm. To fully capture target motion with either MVCT or kV‐CBCT, substantial changes in HU levels up to −600 HU are required which may not be feasible clinically depending on the target's location and surrounding tissue contrast. This registration method, utilizing a substantially decreased window and level compared to standard low‐density settings, was retrospectively compared to the automated registration algorithm for five lung SBRT patients exposed to pre‐treatment kV‐CBCT image guidance. Differences in registrations in the super‐inferior (SI) direction greater than the commonly used ITV to PTV margin of 5 mm were encountered for several cases. In conclusion, pre‐treatment image guidance for lung SBRT targets using MVCT or kV‐CBCT is unlikely to capture the full extent of target motion as defined by the ITVT and additional caution is warranted to avoid registration errors for small targets and patients with LE respiratory traces.